Therapeutic Use of G4-Ligands in Cancer: State-of-the-Art and Future Perspectives - Sara Iachettini; Annamaria Biroccio; Pasquale Zizza (MDPI AG, 2024)
G-quadruplexes (G4s) are guanine-rich non-canonical secondary structures of nucleic acids that were identified in vitro almost half a century ago. Starting from the early 1980s, these structures were also observed in eukaryotic cells, first at the telomeric level and later in regulatory regions of cancer-related genes, in regulatory RNAs and within specific cell compartments such as lysosomes, mitochondria, and ribosomes. Because of the involvement of these structures in a large number of biological processes and in the pathogenesis of several diseases, including cancer, the interest in G4 targeting has exponentially increased in the last few years, and a great number of novel G4 ligands have been developed. Notably, G4 ligands represent a large family of heterogeneous molecules that can exert their functions by recognizing, binding, and stabilizing G4 structures in multiple ways. Regarding anti-cancer activity, the efficacy of G4 ligands was originally attributed to the capability of these molecules to inhibit the activity of telomerase, an enzyme that elongates telomeres and promotes endless replication in cancer cells. Thereafter, novel mechanisms through which G4 ligands exert their antitumoral activities have been defined, including the induction of DNA damage, control of gene expression, and regulation of metabolic pathways, among others. Here, we provided a perspective on the structure and function of G4 ligands with particular emphasis on their potential role as antitumoral agents. In particular, we critically examined the problems associated with the clinical translation of these molecules, trying to highlight the main aspects that should be taken into account during the phases of drug design and development. Indeed, taking advantage of the successes and failures, and the more recent technological progresses in the field, it would be possible to hypothesize the development of these molecules in the future that would represent a valid option for those cancers still missing effective therapies.